Simptomi in znaki s področja spodnjih dihal v ambulanti družinskega zdravnika - Kopčavar Guček, Nena (Medicinski razgledi, 2012)
Cough, dyspnea.chest pain, wheezing, hemoptysis, hemoptoe, abnormal breathing patterns and sputum are the main symptoms of lower respiratory tract disease, which can easily be recognized via a thorough examination of medical history in a family practice. The specificity of the symptoms varies greatly. While cough can indicate the involvement of several organs, wheezing is highly indicative of lower respiratory tract disease. This article discusses some of the lung symptoms and signs, their characteristics and differential diagnoses. Attentive history, followed by precise clinical examination, risk assessment, pro per diagnosis and timely treatment of lower respiratory tract symptoms guarantee successful treatment of patients in family practice settings.
Keywords: kašelj; dispneja; tahipneja; hipopneja; bradipneja; apneja; bolečina v prsnem košu